DINAMIKA IZIN LINGKUNGAN INDUSTRI DAN PENANGANAN PENCEMARAN DAERAH ALIRAN SUNGAI (DAS) CITARUM - Wahyu Fahmi Rizaldy (JURNAL DARUSSALAM: Pemikiran Hukum Tata Negara dan Perbandingan Mazhab, 2024)
This study explores the multidimensional dynamics of the prohibition of polyandry, a marital practice where a woman has more than one husband. Methodologically, the research is grounded in a qualitative approach, drawing on a diverse range of literature, including books, journals, and websites, which are analyzed descriptively and analytically based on the theory of Maslahah. The study aims to provide a deeper understanding and analysis of the dynamics surrounding the prohibition of polyandry and its relevance to the concept of Maslahah. The exploration reveals that the prohibition of polyandry is influenced by social, legal, cultural, economic, and health dimensions. From a social perspective, polyandry disrupts patriarchal structures and complicates issues of lineage and inheritance. Legally, the practice challenges administrative regulations and civil status, reflecting dominant religious and moral norms that support monogamy or controlled polygamy. Economically, while polyandry may address financial constraints in specific settings, it generally reduces economic efficiency and household financial management in the broader societal context. In terms of health, the practice poses risks related to sexual and reproductive health, potentially increasing the spread of sexually transmitted diseases and complicating reproductive management. Additionally, through the lens of Maslahah in Islamic law, the prohibition of polyandry is considered an effort to protect the public welfare, minimize harm (mudharat), and enhance social and familial stability. It indicates that the prohibition policy is not only a manifestation of traditional or religious values but also the result of pragmatic and comprehensive consideration of its long-term impacts on the structure and function of society. Overall, the study provides a critical explanation of how the concept of Maslahah justifies the prohibition, ultimately aiming to preserve societal order and overall well-being.